Strategies for optimising blood glucose control in diabetes mellitus. Issue 4 (April 2021) - Swaby, Rabbi; Randell, Tabitha
Abstract: This article provides an overview of the care of children and young people with Type 1 Diabetes, providing a guide on their management and strategies which can be employed to optimise their blood glucose control. Management strategies such as basal bolus regimens and insulin pump therapies provide multiple options for the paediatrician caring for a child with diabetes. The advancement of technologies in pump therapy and continuous glucose monitoring provide further possibilities, offering more intensive control, improved safety and better quality of life for these children and their families. If the full benefit of technological advancements is to be delivered then this requires input from an effective multi-disciplinary team. We briefly discuss their roles and potential contribution to improved outcomes.